Invisibility as Modern Racism: Redressing the Experience of Indigenous Learners in Higher Education - Amy R. May; Victoria McDermott (Central States Communication Association, 2021)
Indigenous Peoples represent the smallest group of ethnic minorities in the United States, and they are significantly underrepresented in the academy. The tumultuous relationship between institutions of higher learning and First Nation Peoples can be explained in part by the use of education to colonize and force the assimilation of Native Peoples. The end result of centuries of dehumanization and marginalization is invisibility, "the modern form of racism used against Native Americans" (the American Indian College Fund, 2019, p. 5). Educators are challenged to identify institutional inequities and redress barriers to promote social justice through informed and genuine practice, indigenization, and curriculum development that reflects intercultural communication competence.